Does chronic venous insufficiency affect cardiac functions? A speckle tracking echocardiography study - Koca, Fatih; Levent, Fatih; As, Ahmet Kağan; Köksal, Fatih; Tatlı, Ahmet Burak; Vatansever, Fahriye; Demir, Mehmet; Tenekecioğlu, Erhan (The European Research Journal, 2023)
Objective: The aim of this study was to investigate whether there is subtle cardiac dysfunction in patients with chronic venous insufficiency. Methods: Age and sex matched 56 patients with a score of C3 and above in the Clinical, Etiological, Anatomical, Pathophysiological classification and 56 healthy volunteers were included in the study. All subjects were evaluated by detailed echocardiographic examination, including two-dimensional strain echocardiographic analysis by speckle tracking method. Results: Mitral E wave deceleration time (EDT), E and A wave velocity, E/e' ratio for left ventricle, tricuspid EDT, E/e’ ratio for right ventricle and systolic pulmonary artery pressure were found high as significant statistically in patients groups (p < 0.05). But no any statistically significant difference was observed in other parameters between two groups. Conclusions: There may be an increase in diastolic filling pressures in patients with chronic venous insufficiency due to the increased preload in the supine position. This condition seems to be clinically important in patients at high risk for heart failure due to the presumption of the early treatment of chronic venous insufficiency may reduce the risk of heart failure evolvement.